2020
DOI: 10.3390/ma13173667
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Forming Quality of Laser Dynamic Flexible Micropunching by Laser Pre-Shocking

Abstract: Laser pre-shocking (LPS) was introduced into the laser dynamic flexible micropunching process to refine the grain size of a workpiece to improve the forming quality of punched parts. T2 copper foils with five different grain sizes and seven different laser power densities with and without LPS were used for the experiment. The results showed that the grains are refined and the average surface roughness decreases after LPS. For copper foils annealed at 650 °C, the value of decreases from 0.430 to 0.363 µm. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This is because laser shock plays a positive role in improving the surface roughness and refining the internal grains of the workpiece [ 20 , 21 ]. In our previous work, Zhang et al investigated the grain size effect in micro-punching [ 22 ] and micro-bulging processes [ 23 ], and found that laser pre-shocking (LPS) effectively improved the forming quality of micro-parts. However, the existence of the mold size effect restricts the development of microscale laser dynamic flexible bulging (μLDFB).…”
Section: Introductionmentioning
confidence: 99%
“…This is because laser shock plays a positive role in improving the surface roughness and refining the internal grains of the workpiece [ 20 , 21 ]. In our previous work, Zhang et al investigated the grain size effect in micro-punching [ 22 ] and micro-bulging processes [ 23 ], and found that laser pre-shocking (LPS) effectively improved the forming quality of micro-parts. However, the existence of the mold size effect restricts the development of microscale laser dynamic flexible bulging (μLDFB).…”
Section: Introductionmentioning
confidence: 99%